POLYMERIZATION OF AGAR JELLY ICE CUBE HYDROGEL FROM GRACILARIA SP. SEAWEED EXTRACT THROUGH PHYSICAL GELATION AS AN ALTERNATIVE FOOD COOLING MEDIA - Puspasari, Febriyati; Mustafa, Mustafa; Al Athaya, Muhammad Zada (Universitas Mulawarman, 2026)
The suboptimal utilization of seaweed has the potential to cause environmental impacts and low added value for coastal communities, while the food industry still relies on conventional cooling media that are less sustainable. One alternative environmentally friendly material is agar from the seaweed Gracilaria sp. which is able to form a stable gel at room temperature. This study aims to determine the optimum conditions for the polimerization of the hydrogel